Design and implementation of synchronous line loss electricity consumption information collection system based on Beidou technology - Jiye WANG; Liang SHEN; Linxin WANG; Chengyue YANG (Dianxin kexue)
In consideration of this situation,a technical scheme based on Beidou satellite system was proposed,which could realize the collection of power consumption information and could safely bring Beidou terminal onto concentrators and main station systems.At the same time,it was compatible with the original power consumption collection system to achieve effective coverage of the blind zone.A technology of Beidou short message partition and composition was proposed,which made the transmission of long data packets in the power 376.1 protocol come true.Meanwhile,the platform implements the Beidou multi-card management and pre-buffering mechanism to solve the problems of the delay in issuing commands and data query response.And some mechanisms such as active reporting and timing motion tween call instructions in multi period was introduced in order to make up the packet loss problem in the area of Beidou communication.The technology has been tested,which shows that the success rate of data collection under the situation of equipment normal operation can be up to above 99% and demonstrates the high reliability and safety.